الحماية القانونية للمستهلك في ظل عقود التجارة اإللكترونية - _ولهة شيماء _شريف ريان (جامعة المسيلة, 2024)
دى التطور التكنولوجي الهائل إلى تغييرات كبيرة في النظام القانوني للعقود التقليدية، مما أدى إلى ظهور التعامالت التجارية اإللكترونية. هذه المعامالت، التي تجري في عالم افت ارضي دون وجود مادي لألط ارف، جلبت تحديات اقتصادية وتنظيمية كبيرة. لذا، أصبح من الضروري إيجاد آليات قانونية لحماية المستهلك، الطرف األضعف في هذه العالقة، ا من المرحلة السابقة لتكوينه وصوًال إلى تنفيذ االلت ازمات ً تشمل جميع م ارحل العقد بدء الناشئة عنه، لضمان حقوق المستهلك وتعزيز الثقة في المعامالت اإللكترونية. الكلمات المفتاحية : حماية المستهلك ، التجارة اإللكترونية ، العقد اإللكتروني Abstract : The tremendous technological development has led to major changes in the legal system of traditional contracts, leading to the emergence of electronic business transactions. These transactions, which take place in a virtual world without the physical presence of the parties, have brought significant economic and regulatory challenges. Therefore, it has become necessary to find legal mechanisms to protect the consumer, the weaker party in this relationship, that include all stages of the contract, starting from the stage preceding its formation up to the implementation of the obligations arising from it, to guarantee consumer rights and enhance confidence in electronic transactions. Keywords : Protection des consommateurs, Commerce électronique, Contrat électroniqu
Keywords: حماية المستهلك ، التجارة اإللكترونية ، العقد اإللكتروني